Green Accounting Implementation And CSR Disclosure On Company Profitability With GCG As A Moderating Variable: Case Study on a Listed Energy Company in Indonesia Stock Exchange 2017-2022 - Huwaida, Sarah; Puspitasari, Ratih; Djanegara, Moermahadi Soerja (Institut Bisnis dan Informatika Kesatuan, 2025)
The decline in net profit experienced by several energy companies listed on the Indonesia Stock Exchange (IDX) in 2020, factory emissions causing air pollution, waste disposal into rivers, lakes, and seas leading to water pollution, soil damage, forest degradation, and other forms of environmental destruction that can cause natural disasters, the lack of economic improvement for residents living around mining areas despite the presence of energy companies, and the demands from society and the government for companies to balance business focus with attention to social and environmental conditions. The study aims to examine whether green accounting, CSR, and GCG affect the profitability of energy companies listed on the Indonesia Stock Exchange from 2017 to 2022. This research is quantitative, and the sampling method used to determine the research sample is purposive sampling. The results of the study, using multiple linear regression analysis and moderated regression analysis, show that green accounting, CSR, and good corporate governance negatively correlate with and impact company profitability. Also, GCG as a moderating variable can strengthen the relationship between green accounting and company profitability but does not strengthen the relationship between CSR and profitability. Keywords: Green Accounting, Corporate Social Responsibility (CSR), Good Corporate Governance (GCG)